ANALISIS PENGARUH AUDIT INTERNAL, KARAKTERISTIK PERUSAHAAN DAN NET PROFIT MARGIN TERHADAP IMPLEMENTASI SISTEM MANAJEMEN ANTI PENYUAPAN: ANALISIS PENGARUH AUDIT INTERNAL, KARAKTERISTIK PERUSAHAAN DAN NET PROFIT MARGIN TERHADAP IMPLEMENTASI SISTEM MANAJEMEN ANTI PENYUAPAN - Wahyu Firmansyah; Nurhastuty Kesumo Wardhani (KRISNA: Kumpulan Riset Akuntansi, 2025)
The occurrence of fraud or corruption cases involving all elements both carried out by company management and regulators by working together to launder the proceeds of corruption or working together to manipulate government projects in Indonesia has caused public trust and stakeholders to decline. The government has issued guidelines for public and private organisations in implementing the ISO 37001:2016 Anti-Bribery Management System (ABMS), which aims to empower corruption prevention efforts in private and non-profit environments to control bribery practices and implement an anti-corruption culture within the company. To prevent corruption in the construction services industry, one of the simplest methods used is to increase awareness at the management and employee levels to always be aware of everything that surrounds them. This study aims to analyze the effect of internal audit and company characteristics on the implementation of the Anti-Bribery Management System (ABMS). The object of research is infrastructure sector companies in the 2021-2023 period. The data analysis is quantitative and uses secondary data obtained from the IDX website. The analytical tool used is SPSS Version 25 by processing data starting with the normality test, classical assumption test, multiple linear analysis, hypothesis testing. The research results obtained that internal audit has a significant effect on the anti-bribery management system, company size and age have a significant effect on the anti-bribery management system and Net profit margin has no significant impact on the anti-bribery management system.